Implications of Ecofeminism in Efforts to Preserve the Environment of Coastal Settlements - Hidayati, Nanik; Sunandar, Muhamad Aris (Indonesian Journal of Advanced Research, 2024)
Coastal ecofeminism is women's concern for the environmental conditions of coastal settlements which are synonymous with slum settlements. The aim of this research is to analyze the implications of ecofeminism in efforts to preserve the coastal settlement environment in terms of ecological, psychological, economic, social, cultural and disaster mitigation aspects. The research object is the coastal settlements of Kendal Regency which stretches from Tawang to Kaliwungu. The research subjects are the coastal communities of Kendal Regency, communities and related agencies. This research uses descriptive qualitative phenomenological research methods to present the results of observations, interviews and field documentation. The results obtained in this research are that coastal ecofeminism needs to be supported by all parties so that there is sustainability. In the ecological, cultural and disaster mitigation aspects, ecofeminism needs to be supported so that the sustainability of coastal settlements is maintained. In the economic aspect, society needs strengthening and policies for business and MSME development. In the psychological aspect, women are given psychological protection and counseling, especially those who have experienced trauma healing from domestic violence or broken homes.